Why not to choose the most convenient labor supply model? The impact of labor supply modeling on policy evaluation - Georg Hirte; Stefan Tscharaktschiew (European Regional Science Association (ERSA), 2015)
The public economics, environmental, transportation and urban economics literature applies different labor supply approaches when studying economic or planning instruments. Some studies assume that working hours are endogenous while the number of workdays is given, whereas others model only decisions on workdays. Unfortunately, empirical evidence does hardly exist on account of missing data. Against this background, we provide an assessment of whether general effects of those policies are robust against the modeling of leisure demand and labor supply. We introduce different modeling approaches into a spatial general equilibrium model and discuss how they affect the welfare implication of several policies. We, then, perform simulations and find that in many cases the choice of labor supply modeling not only affects the magnitude of the policy impact but also its direction. While planning instruments are suggested to be quite robust to different labor supply approaches, the way of modeling labor supply may crucially affect the overall welfare implications of economic instruments such as congestion tolls. Based on these findings it becomes clear which labor supply approach is the most appropriate given specific conditions. Our study also emphasizes the need for better micro labor market data that also feature days of sickness, overtime work, the actual number of leave days, part-time work, telecommuting etc.
Keywords: H2; H3; J22; Q5; R1; R4; R5; 330; Urban Economics; Tax Effciency; Labor Supply; Transportation Economics